Atmospheric forcing by ALADIN/MFSTEP and MFSTEP oriented tunings - R. Brožková; M. Derková; M. Belluš; A. Farda (Ocean Science, 2006)
ALADIN/MFSTEP is a configuration of the numerical weather prediction (NWP) model ALADIN run in a dedicated real-time mode for the purposes of the MFSTEP Project. A special attention was paid to the quality of atmospheric fluxes used for the forcing of fine-scale oceanographic models. This paper describes the novelties applied in ALADIN/MFSTEP initiated by the MFSTEP demands, leading also to improvements in general weather forecasting.